Sharia Stock Return Anomalies In Indonesia: Study of Literature And Postgraduate Students' Perspectives (International Journal of Cultural and Social Science, 2022)
Investment is an activity to invest funds in a company that is carried out by investors within a certain period of time with the expectation of future results. One type of investment in the capital market. However, there are studies which state that there are deviations or anomalies in the concept of efficient markets. This research is a qualitative research by conducting a literature study of 32 papers from a search on the Google Scholar database with the keyword “Abnormal Return” or Anomalies and Return and “Sharia Shares” in the period 2017 to 2021. The search process uses the help of the Publish Or Perish application. Furthemore, the research was conducted by interviewing S2 Syariah Banking students in 2021 at the State Islamic University of North Sumatra. The results of this study indicate that there are several types of return anomalies that occur in Islamic stocks, Firm Anomalies, January Effect, Day of the Week Effect, Accounting Anomalies, Holiday Effect. However, this anomaly of Islamic stock returns does not always occur in Islamic stocks in Indonesia.